The experience of the infant entering refuge (shelter) setting with their mothers after fleeing family violence - Bunston, Wendy (Journal of family violence, 2021)
Almost nothing is known about how the infant may experience being in a women’s Refuge (Shelter) setting with their mother after fleeing family violence, despite the high numbers of infants and young children in Refuges or Shelters. This research was concerned with exploring how the infant experienced refuge within a Refuge setting post family violence. Using a non-intrusive, ethically informed, ‘infant led’ approach, this research involved ten infants (aged 3 weeks to 16 months), ten mothers, and 13 staff in eight Refuges from three countries: Australia, Scotland and England. Data was collected through infant observation, interviews with mothers and then staff. Presented is a synthesis of a research methodology which was led by the infant, drew on concepts of ‘inter-subjectivity’ and used a constructivist grounded theory method. Infants were often lost from view within the Refuge setting. The mother, herself traumatised, was expected to be the refuge for her infant. Only the obviously distressed infant was assisted, and where available, from outside specialist workers. It was often too painful for the adults, both mothers and staff, to see or reflect on the infant’s possible trauma. Significantly, in all cases the motivation for each mother to enter Refuge was ensuring their infant’s safety. Concern for their infant or young child can be a powerful catalyst for women leaving a violent relationship. Refuges (Shelters) are in a unique position to respond to the infant in their own right whilst helping to heal and grow the infant/mother relationship.